Tadris Maharah Al-Qiroah li An-Nathiqiin bi Ghairiha Al-Usus An-Nazhariah wa Al-Istiratijiyat At-Tathbiqiyah - Sanaa Allal Lahlali (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2021)
This research paper highlights the reading skill in teaching Arabic to other speakers as a receptive skill (listening-reading) that contributes to enriching the learner's language ammunition. The research is made up of two parts: a theoretical part: it focuses on the importance of reading skill, while presenting its types and the purpose of its teaching. And a practical one which deals with the most important strategies used while presenting a reading lesson. This research paper is based on theoretical ideas derived from the heart of applied linguistics, as well as from applied study based on, on the one hand, an educational experience that I have gained while teaching non-Arabic speakers from different countries and nationalities, as well as benefiting from some training courses developed by academic specialists in Arabic language education for nonnative speakers of Arabic.  On the other hand, it benefits from specialized and varied linguistic sources and references.تروم هذه الورقة البحثية تسليط الضوء على مهارة القراءة في مجال تعليم اللغة العربية للناطقين بغيرها؛ باعتبارها من المهارات الاستقبالية (الاستماع- القراءة) التي تسهم في إغناء الذخيرة اللغوية لدى المتعلم. ويتكون البحث من شقين: شق نظري: تطرق لماهية القراءة وأهميتها، مع عرض أنواعها والهدف من تدريسها. وشق تطبيقي تم فيه عرض أهم الاستراتيجيات المتبعة في تقديم القراءة. تستند هذه الورقة البحثية إلى أفكار نظرية مستمدة من صميم اللسانيات التطبيقية، و وإلى دراسة تطبيقية ميدانية ترتكز – من جهة – على تجربة تربوية خضناها في تدريس الناطقين بغير العربية من دول وجنسيات مختلفة، فضلا عن استفادتي – حضوريا – من بعض الدورات التدريبية التي أطرها خبراء دوليون. وترتكز من جهة أخرى على مصادر ومراجع لسانية متخصصة ومتنوعة.